(untitled) - Howard, Ethel (London, 1918)
The contents of this book are primarilly personal experiences of a seven years' stay in the house of a Japanese nobleman, having been gleaned from jotting in my diary and such reminiscences as my memory recalls.
Keywords: Nhật Bản,Japan; Đời sống xã hội và phong tục,Social life and customs